2019
DOI: 10.31327/jee.v4i1.859
|View full text |Cite
|
Sign up to set email alerts
|

The Students and Teacher’s Views on the Use of E-Textbooks in Reading Classroom

Abstract: Since the development of information technology grows rapidly, the educational institutions are offered various media or tools of instruction supporting and enhancing teaching and learning process. E-textbooks are a variety of technology which changes the experience of classroom language from traditional into paperless in reading classroom. This technology facilitates the teacher and the students to utilize computer and paper-based reading tasks in realizing the functions of the e-learning environment. It crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…The end-of-semester questionnaire and interviews indicated that although the majority of the participants were experienced digital readers and were in general receptive to e-textbooks, the participants did not overwhelmingly prefer to read digitally. The finding reflected what was mentioned in the studies such as Nopiyanti and Tarjana (2019) and also Verkijika (2019). Even with the same note-taking and highlighting features as print books, roughly half of them still preferred conventional paper textbooks.…”
Section: Reserved Attitude Toward E-textbookssupporting
confidence: 80%
See 1 more Smart Citation
“…The end-of-semester questionnaire and interviews indicated that although the majority of the participants were experienced digital readers and were in general receptive to e-textbooks, the participants did not overwhelmingly prefer to read digitally. The finding reflected what was mentioned in the studies such as Nopiyanti and Tarjana (2019) and also Verkijika (2019). Even with the same note-taking and highlighting features as print books, roughly half of them still preferred conventional paper textbooks.…”
Section: Reserved Attitude Toward E-textbookssupporting
confidence: 80%
“…The purpose of the study is to investigate whether an e-textbook brings facilitative effects on university students' reading whose English proficiency was low. EFL English teaching is continuously evolving through the adoption of more innovative methods to engage students so that they can become more motivated to learn (Jung et al, 2019;Nopiyanti & Tarjana, 2019). E-textbooks are treated as a pedagogical tool (Cuillier & Dewland, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…All questions and explanations were in Indonesian to create a relaxed atmosphere and to enable students to understand instruction. In this study, the closed questionnaire was adapted from Nursanti (2016) which included four answers such as strongly agree, agree, strongly disagree, and disagree. Before giving the questionnaire, the researcher also observed 80 minutes or two hours of learning activities in the English class to see the emergence of Indonesian.…”
Section: Methodsmentioning
confidence: 99%
“…Depending on the selection and use of the materials and methods, there come drastic changes in the learning process. Hence, prominent researchers like Kabir (2023); Abduh et al (2022); Al Amin and Greenwood (2022); Bhuiyan and Khan (2022); Deressa et al (2022); Hosan and Weiyan (2022); Oeamoum and Sriwichai (2020); Nuby et al (2019); Rahman (2019); Khanom (2018); ; ; Alam (2017); Ray and Roy (2017); Cakir (2015); Rahman and Karim (2015); Mitu (2014); Rasul (2014); Diniah (2013); Salahuddin et al (2013); Mamun et al (2011); Harsono (2007), etc. tried to work on these issues from their perspectives.…”
Section: Literature Reviewmentioning
confidence: 99%